Do external labor market incentives motivate CEOs to adopt more aggressive corporate tax reporting preferences? - Kubick, Thomas R.; Lockhart, G. Brandon (Journal of Corporate Finance, 2016)
Building on recent theory, we find strong and robust evidence that external labor market incentives motivate CEOs to adopt more aggressive tax policies in order to improve firm performance and their own labor market value. In addition, we find that the tax aggressiveness-labor market incentives relation varies in the cross-section consistently with theory. We find that the relation is attenuated in industries for which the CEO has fewer outside employment options, and we find it to be amplified in industries for which competition for CEO talent is likely greatest, and also among CEOs estimated to have greater ability. Overall, our results suggest that the market for CEOs – an incentive device external to the firm – has a meaningful impact on corporate tax policy.